And Baby Makes Three: Kindling the Reciprocal and Dynamic Processes of Caregiving. (3rd April 2019) - Lin, Hung-Chu; Bisson, Jennifer B.; Sanborn, Sarah M.
SYNOPSIS: Hechler et al.'s (2019) utilization of a simulation paradigm to predict postnatal caregiving quality is worth celebrating. Instead of using subjective self-report measures, the authors objectively observed behaviors that potentially mapped onto real-life processes. As well, they considered for regulatory processes and included fathers into the picture of early caregiving. To enhance the prediction of caregiving simulation paradigms, we advocate for paradigms that are interactive in nature and address the unique roles of the infant, the mother, and the father. Effective paradigms afford context-specific conclusions that sufficiently address the dynamic qualities of iterative interactions between the infant and parents.